Gossypium latifolium genome reveals the genetic basis of domestication of upland cotton from semi-wild races to cultivars - Chao Fu; Nian Wang; Qingying Meng; Zhiyong Xu; Yu Le; Xianlong Zhang; Yangyang Wei; Renhai Peng; Chao Shen; Zhongxu Lin (Crop Journal)
The genetic basis for Gossypium hirsutum race latifolium, the putative ancestor of cultivated upland cotton, emerging from the semi-wild races to be domesticated into cultivated upland cotton is unknown. Here, we reported a high-quality genome assembly of G. latifolium. Comparative genome analyses revealed substantial variations in both gene group composition and genomic sequences across 13 cotton genomes, including the expansion of photosynthesis-related gene groups in G. latifolium compared with other races and the pivotal contribution of structural variations (SVs) to G. hirsutum domestication. Based on the resequencing reads and constructed pan-genome of upland cotton, co-selection regions and SVs with significant frequency differences among different populations were identified. Genes located in these regions or affected by these variations may characterize the differences between G. latifolium and other races, and could be involved in maintenance of upland cotton domestication phenotypes. These findings may assist in mining genes for upland cotton improvement and improving the understanding of the genetic basis of upland cotton domestication.